Economic Analysis for the Existing PV Supplier to Decide Whether to Install ESS or Not in South Korea - Kong, Junhyuk; Lee, Wonjun; Jung, Jaesung (International Conference on Innovative Smart Grid Technologies, ISGT Asia 2018, 2018)
This paper presents the economic analysis when Photovoltaic (PV) generator combines with Energy Storage System (ESS) in South Korea. For this, the current government policy and compensation rule are investigated including Renewable Portfolio Standard (RPS) and Renewable Energy Certificate (REC). Under these policies, the economic analysis provides an effective guideline for existing PV generation supplier to decide whether to install ESS or not. It is determined based on Net Present Value (NPV) by considering the investment cost of ESS. The actual data is used to simulate the economic analysis by calculating the expected revenues of PV generator without and with ESS.
Keywords: Energy storage systems; Expected revenue; Investment costs; Net present value; Photovoltaic; PV generation; Renewable energy certificates; Renewable portfolio standard; Economic Analysis; Energy Storage System (ESS); Photovoltaic (PV); Renewable Energy Certificate (REC); Renewable Portfolio Standard (RPS)